Principals of Active Learning Strategies for Islamic Education Teachers in Zarqa Governorate - Yasen, Omar Abdelaziz Mosa (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the degree to which Islamic Education Teachers possess the principles and strategies of active learning In Government Schools of the Education Directorate in the Zarqa governorate (1). The descriptive approach was used and to achieve the objectives of the study, a questionnaire was used as a tool for data collection; it consisted of (27) paragraphs, which applied on a sample of (72) male teachers and (88) female teachers. The result showed that the level of Degree to which Islamic Education Teachers possess the principles and Strategies of active learning was High with (3.92) score The findings also showed there were no statistically significant differences between the level of Islamic Education teachers sex (male and female) in addition there were statistically significant differences between teachers of (5 years and less) of experience and these with (5-10) years of experience in favor of the second group and statistically significant differences between teachers of (5-10) years of experience and these with (10 and more) years of experience in favor of the second group. In light of these findings, the researcher suggested a set recommendation including the necessity of holding training courses for teachers and students to explain the role of each other in light of active learning.